Analisis Transformasi Kelembagaan Ekonomi Peternak Kambing Menjadi Badan Usaha Milik Petani (BUMP) (Studi Kasus Kelompok Ternak di Kecamatan Borobudur – Kabupaten Magelang) - F. Achmad; H. T. Wibowo; E. Purwono; H. Nurzayyan; D. A. K. Masrocha; S. Prabowo (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The capacity of farmer group institutions in Indonesia is expected to be increased to become FarmerOwned Business Entity (BUMP) in order to further empower the farmer group members. This study aimed to analyze the institutional level of goat farmer groups in Borobudur District, Magelang Regency, and the relationship between group business entity indicators and the preparation for BUMP Establishment. The data were enumerated with the Likert scale, with three levels of scoring, using a questionnaire, and the accumulation of the total score was classified into low (120 to 200), moderate (200 to 280), and high (280 to 360). Subsequently, the structural equation modeling (SEM) analysis and path analysis were performed. The results of the study indicated that the institutional level of goat farmer groups in Borobudur District, Magelang Regency, was at a moderate level, and there were 2 (two) variables that influence the establishment of BUMP at a 95% confidence level (P<0.05), namely the farmer group’s institutional performance and the farmer group’s institutional organizational management variable. Corrective programs to elevate the farmer business institutional levels in Magelang should emphasize the institutional performance and organizational management aspects as final counsel.